Reviving the Inert: Deciphering Order 58 Rule 3(2) of the High Court Civil Procedure Rules, 2004 (C.I. 47) through the Lens of Springfield Energy Ghana Ltd. V. Bulk Oil Transportation and Storage Company PLC (Global Journal of Management and Business Research, 2023)
In today s dynamic global economy jurisdictions like the Ghanaian legal system have recognized the significance of promoting efficient economic trade and commerce thus the revolution of economic laws Despite the efforts the ever changing complex nature of commercial disputes has been unmatched To augment soft law strategies the Rules of Court Committee hath formulated novel regulations for the administration of commercial cases These rules are a deviating of the traditional rules of procedure In essence this paper delves into the recent nuances that govern summary judgments in commercial cases within the Ghanaian jurisdiction The mechanic is pivoted on the stages at which aggrieved parties can leverage on summary judgment provisions in furtherance of their case In conclusion it will unravel the current sphere of dispute resolution in the realm of commerce within the Ghanaian jurisdiction
Keywords: summary judgment; amendment and revocation; constitutional instrument; pre-trial settlement conference